2005
DOI: 10.1110/ps.051718605
|View full text |Cite
|
Sign up to set email alerts
|

Gateway vectors for the production of combinatorially‐tagged His6‐MBP fusion proteins in the cytoplasm and periplasm of Escherichia coli

Abstract: Many proteins that accumulate in the form of insoluble aggregates when they are overproduced in Escherichia coli can be rendered soluble by fusing them to E. coli maltose binding protein (MBP), and this will often enable them to fold in to their biologically active conformations. Yet, although it is an excellent solubility enhancer, MBP is not a particularly good affinity tag for protein purification. To compensate for this shortcoming, we have engineered and successfully tested Gateway destination vectors for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
133
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 153 publications
(137 citation statements)
references
References 27 publications
3
133
0
Order By: Relevance
“…It is possible that different solubility-enhancing proteins work by different mechanisms, or even by utilizing more than one mechanism, although comparative studies with MBP and E. coli NusA seem to suggest otherwise [12]. In any case, the results presented here are most consistent with the proposal that MBP posesses intrinsic chaperone-like qualities in the context of a fusion protein, and that the hydrophobic ligand-binding cleft plays a central role in its mechanism of action.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…It is possible that different solubility-enhancing proteins work by different mechanisms, or even by utilizing more than one mechanism, although comparative studies with MBP and E. coli NusA seem to suggest otherwise [12]. In any case, the results presented here are most consistent with the proposal that MBP posesses intrinsic chaperone-like qualities in the context of a fusion protein, and that the hydrophobic ligand-binding cleft plays a central role in its mechanism of action.…”
Section: Discussionsupporting
confidence: 77%
“…Next, the amplicons from these two PCRs were combined and used as the template for another PCR with primers PE-42 and PE-1425. The resulting PCR amplicon was digested with BglII and NotI, and then inserted between the unique BglII and NotI sites in pDEST-HisMBP [12] to generate an otherwise idential derivative of pDEST-HisMBP encoding the DM mutant MBP. Derivatives of pDEST-HisMBP encoding the I329W, W62E/Y155E, and W230E/W340E mutant MBPs were constructed with a QuickChange Site-Directed Mutagenesis kit (Stratagene).…”
Section: Construction Of Mutant His-mbp Destination Vectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, however, amylose affinity chromatography has proven to be problematic at times, not only because of the relatively low binding capacity of amylose resin for MBP but also because of persistent contaminants that require additional chromatographic steps to remove (5)(6)(7). We have demonstrated that a hexahistidine tag (His 6 ) can be added to the N-terminus of MBP without interfering with its ability to promote the solubility of its fusion partners (8). Therefore, IMAC can be used to circumvent the problems associated with amylose affinity chromatography.…”
mentioning
confidence: 99%